Implementasi Program Dandan Omah di Kelurahan Bulak Banteng Kota Surabaya - Vidya Imanuari Pertiwi; Asiel Bernike Remalya; Lucy Cita Widya Amanda; Rizky Buana Sari; Widya Larasati (VISA: Journal of Vision and Ideas, 2024)
The city of Surabaya, as the capital of East Java province, still faces unresolved poverty issues. According to data from the National Socio-Economic Survey, Surabaya experienced the highest growth in uninhabitable houses between 2016 and 2020, reaching 27.11 percent. The Surabaya City Government, as an autonomous region with rights and obligations, demonstrates its commitment to meeting the basic needs of its residents through a housing program known as the Uninhabitable House Program or ‘Dandan Omah.’ In Bulak Banteng Subdistrict, where inadequate housing conditions persist, 24 households received assistance through the home improvement program in 2023. This research applies Richard Matland’s theory, which includes four indicators of policy implementation: policy accuracy, implementation accuracy, target accuracy, and environmental accuracy. The first indicator suggests that this policy effectively improves the welfare of Bulak Banteng residents by providing habitable homes. However, implementation accuracy remains a challenge, as it does not fully align with established regulations and guidelines, particularly in document processing. Despite this, the chosen intervention targets match the plan and avoid overlap with other programs, representing an enhancement over previous policies. Additionally, the policy environment involves interactions between the Surabaya City Public Housing and Settlement Area, the Defense Department (DPRKPP), the Bulak Banteng Subdistrict, and the Bulak Banteng Home Repair Technical Group (KTPR). External factors, including public perceptions, also influence the policy’s effectiveness.